Robust static output-feedback stabilization for nonlinear discrete-time systems with time delay via fuzzy control approach. - Song-Shyong Chen
This paper addresses the problem of designing robust static output-feedback controllers for nonlinear discrete-time interval systems with time delays both in states and in control input. In the approach, we do not directly employ the Lyapunov approach, as do in most of traditional fuzzy control design approaches. Instead, sufficient conditions for guaranteeing the robust stability for the considered systems are derived in terms of the matrix spectral norm of the closed-loop fuzzy system. The stability conditions are further formulated into linear matrix inequalities so that the desired controller can be easily obtained by using the Matlab linear matrix inequality (LMI) toolbox. Finally, an example is provided to illustrate the effectiveness of the proposed approach.
Keywords: Closed-loop fuzzy system; Fuzzy control design; Linear matrix inequalities; Matrix spectral norm; Nonlinear discrete-time interval system; Robust stability; Robust static output-feedback control; Time delays